Homologia in Thucydides: Form, Function, and Debate (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2024)
In his account of the ‘Peloponnesian War’, Thucydides also describes many capitulation treaties, most of which are referred to as homologies (ὁμολογίαι). Since Thucydides makes use of a legal-technical terminology and the treaties often seem to be designed according to a similar pattern, it is argued in the literature that Thucydides consulted original documents and, based on their wording, integrated them into his work, perhaps even quoted them. The corpus of these ὁμολογίαι will be analysed in this study on the basis of three questions: (1) What terminology does Thucydides use? (2) How is the treaty-making process presented? (3) How does Thucydides refer to the respective performance content of a ὁμολογία? On this basis, international law can also make a valuable contribution to the current heated debate on the structure and significance of homology in the 5th/4 th century BC.
Keywords: ὁμολογία; Thucydides; legal terminology; documents in litrerary sources; international law in the fifth century BC